Timing of first prenatal ultrasound and associated factors among women who gave birth at health institutions in Ambo Town, central Ethiopia - Samson Mesfin; Gizachew Abdissa Bulto; Motuma Gutu; Natnael Dechasa Gemeda (PLoS ONE, 2025)
Background The Ethiopian Ministry of Health recommends “one prenatal ultrasound scan before 24 weeks of gestation for every pregnant woman.” Despite clear suggestions for timely prenatal ultrasound utilization, little is known about the extent to which it is utilized and the factors affecting the timing of the first prenatal ultrasound examination in the study area. Hence, this study aimed to assess the timing of the first prenatal ultrasound and identify associated factors among women who delivered at health institutions in Ambo town, central Ethiopia. Methods This health facility-based cross-sectional study was conducted from September 12 to October 30, 2022. Data were collected through interviews using structured questionnaires and record reviews. A total of 442 participants were recruited through systematic random sampling. Data analysis was performed using a binary logistic regression model in SPSS Version 25. Adjusted odds ratios with a p-value of less than or equal to 0.05 were used to declare statistical significance. Results Overall, 71% (95%CI: 67.0–75.6) of participants had received a timely prenatal ultrasound. Living in urban areas (AOR = 5.64,95%CI:2.53–12.55), having a history of prenatal ultrasound during previous pregnancy (AOR = 2.47,95%CI:1.24–4.89), attending ANC visits at hospital (AOR = 3.30,95%CI:1.19–9.16), and good knowledge of prenatal ultrasound (AOR = 4.46,95%CI:2.26–8.81) were found to significantly affecting the timing of the first prenatal ultrasound. Conclusion In this study, more than a quarter of the women did not receive timely prenatal ultrasounds. Urban residence, previous use of prenatal ultrasound, attending ANC at the hospital, and having good knowledge were factors identified for timely prenatal ultrasound. Therefore, all stakeholders must work on those identified factors to improve the timely ultrasound scanning.